(3LHQG GHQGgje LHQG(B- (3LPhQ Gdaf GdYQGbjs - Jabra, Ibrahim Jabra; (3LHQG GHQGgje LHQGs ((3HZOGO; s (3GdOGQ GdYQHjI;s, 1986)
(3cGf Gdaf aj hGOj GdQGaOjf OGFekG cTYH gPG GdhGOj, cdGgeG fJGL GdCQV hGdefGN(B. (3cdGgeG de jOQc bW GdGfMWGW hde jHdZ bW GdceGd(B: (3aceGd GdUfYI, HGdfSHI Edjg, jMO ef GdJYHjQ GdPGJj(B. (3cGf Yed GdafGfjf GdYQGbjjf GdbOGei NTfkG hdcfg Zfj HGdGHJcGQ(B. (3ajg MjhjI hLQCI dG JJjSQGf ddJbfjI GdeQgaI(B. (3hcGf GdafGf OGFekG MQkG aj GdJYHjQ Yf faSg, MJi aj NVe af GdOhdI aj BThQ , MjK jJcde GdafGf GdMbjbj ef NdGd OQGeI GdMjhGf GdLQjM(B.s
Arabic
Keywords: N61-72 Theory. Philosophy. Aesthetics of the visual arts; Iraq